Resiliência informacional: modelo baseado em práticas informacionais colaborativas em redes sociais virtuais - Brasileiro, Fellipe Sá (2017)
This research aims to explain, through a model, the circumstances in which information and collaborative practices that happens on the contexts of virtual spaces, linked to mobile communication devices, make possible the construction of informal resilience and development of informative competences needed to transition on complex environments in uncertainty times. Part of the hypothesis that collaborative informational practices measured by virtual spaces make possible the construction of informational resilience as long as they turn possible a social cohesion negotiated and constructed on interaction situations. The theoretic dimension that sustain the hypothesis of work is structured on Randall Collins’ Ritual Interaction Theory (2004) and its expansion on the perspective of Ling (2008) for the context of interactions mediated by mobile technologies. Methodologic dimension is structured on the combination of two methodologic scopes – study of case and retrospective study. Study of case develops around a group of women that experienced maternity for the first time and used web spaces, specifically the WhatsApp instant messaging application, as an informational strategy aiming to face collectively the uncertainties that emerges on this context. Retrospective study – involving procedures of data sample and analysis – develops based on the method of Collective Subject Discourse. Results found demonstrate that collaborative practices mediated by virtual spaces spaces are effectively managed, negotiated and coordinated from the moment that participants experience a collective conscience – regarding an informational strategy of web collective facing – directed to the common good. This collective conscience, on turn, is the result of an intense emotional shared experience emerging from situational microdynamics of tecnomediated interactions and generates individual and collective feelings/values/emotions necessary to the construction of informational resilience and development of informational competences – on negotiated, situational, creative and alternative forms – face to informative restrictions that individualize living contexts. We concluded that informational resilience model in virtual social networks can be configured as a methodologic resource to competitive studies, informational practices and information politics based on personal/significative/medic contexts once it reveals a microdynamics of collaborative practices that can structure the process of informational resilience on virtual environments and, at the same time, guide the mediation actions of information providers linked to mobile communication devices. It evidences that usage of this technologies as a strategy of an information politic for development of informational competences in collectives on adversity situations implies an articulation between situational dimension of collaborative practices in virtual social networks (of the subjects in need of intimal informations) and dimension of informational action of credible and scientific information providers.